Personal Branding Pengguna Apple Remaja di Instagram (E-Jurnal Medium, 2022)
The background of the research stems from the widespread use of Apple products, especially by teenagers and the assumption that the quality of Apple products is better than Android, especially for accessing Instagram, so it is believed to increase the personal branding of its users. The theory used in analyzing this research is personal branding theory related to Littlejohn's impression management theory, as well as Computer Mediated Communication (CMC) theory by Tomic, et al. This research uses a qualitative research model by interviewing the tenenagers with an apple addict and observe their Instagram account. The results showed that by using apple product, their personal branding will be upgrade in their relationship, friendship, existence, study and career, entertainment and utility factors. In the process of building personal branding, users showing their Apple products directly and do mirror selfie in order to be recognized by others.